Passando o bastão : o processo de sucessão na empresa familiar sob o ponto de vista do fundador - Moraes, Josenice Regina Blumenthal de (2015)
The multigenerational cycle of succession in family businesses has been the subject of concerns regarding the positioning of the founder. These concerns justify the realization of this dissertation considering the following questioning: in the passing of the baton, what is the viewpoint of the founder of the family business on the succession process? Drawing on perceptions of the founder on the succession process, the researcher attempts to identify how their lives are influenced by this process. In order to achieve these objectives, a qualitative research was carried out, with collective and instrumental case study outlining grounded in the Systemic Approach of the family, in the Three-Dimensional Developmental Model of Family Business, which seeks to differentiate the family relationships from the company context, as well as in the correlation of the business family‟s Development Model and the Family Life Cycle Model. Participating in this study were four family business founders invited by the researcher. The presented data was derived from the records of semi-structured interviews with the participants, as well as from the applied instruments: the Constructivist Genogram and the Family Timeline. Proceeding to the individual data analysis, the results marked the individual differences concerning the life story of each participant, and the viewpoint of each founder on the business succession process during the passing of the baton. The overlapping of the family life cycle and the business family life cycle, and their influence on their lives, were also identified in the analysis results. This study pointed towards the possibility of theoretical probing on the subject, in the Brazilian academic community, through scientific research, which may help comprehend the phenomenon of the founder in the succession process of the family business, in the passing of the baton, within the peculiarities of our country, Brazil